Effect Of Working Capital Management On The Profitability Of Listed Manufacturing Companies In Ghana - Emmanuel Ofori Aidoo (knust, 2025)
I Praise My Lord And Master Jesus For Gracefully Seeing Me Through My Two-Year Studies At The Kwame Nkrumah University Of Science And Technology. I Am Also Deeply Grateful To Knust's Leadership And The Lecturers, Especially The Accounting Department, For Grooming And Supplying Me With The Insight And Academic Capacity I Need To Confront The Global Economy. I Am Also Appreciative Of The Hundreds Of Both Classical And Contemporary Authors And Lecturers Who Have Influenced My Life And Supported Me Continue To Improve My Personality. Finally, Special Gratitude To My Family, Friends, And Other Individuals Who Have Deeply Contributed To The Completion of this research project. May God bless all of you